Congenital malformations and preeclampsia associated with integrase inhibitor use in pregnancy: A single-center analysis. - Christiana Smith; Angela J Fought; Joyce F Sung; Jennifer R McKinney; Torri D Metz; Kirk B Fetters; Sarah Lazarus; Shannon Capraro; Emily Barr; Carrie Glenny; Jenna Buehler; Adriana Weinberg; et al. (PLoS ONE)
Background Antiretroviral therapy (ART) decreases perinatal HIV transmission, but concerns exist regarding maternal and infant safety. We compared the incidence of congenital malformations and other adverse outcomes in pregnancies exposed to integrase inhibitor (INSTI) versus non-INSTI ART. Setting Single-site review of all pregnancies among women living with HIV between 2008 and 2018. Methods We used binomial family generalized estimating equations to model the relationship of congenital anomalies and pregnancy outcomes with exposure to INSTI or dolutegravir (DTG) versus non-INSTI ART. Results Among 257 pregnancies, 77 women received ≥1 INSTI (54 DTG, 14 elvitegravir, 15 raltegravir), 167 received non-INSTI, and 3 had missing data. Fifty congenital anomalies were identified in 36 infants. Infants with first-trimester DTG or any first-trimester INSTI exposure had higher odds of congenital anomalies than infants with first-trimester non-INSTI exposure (OR = 2.55; 95%CI = 1.07-6.10; OR = 2.61; 95%CI = 1.15-5.94, respectively). Infants with INSTI exposure after the second trimester had no increased odds of anomalies. Women with INSTI exposure had higher odds of preeclampsia (OR = 4.73; 95%CI = 1.70-13.19). Among women who received INSTI, grade ≥3 laboratory abnormalities were noted in 2.6% while receiving the INSTI and 3.9% while not receiving the INSTI, versus 16.2% in women who received non-INSTI. There was no association between INSTI exposure and other pregnancy outcomes. Conclusion In our cohort, first-trimester INSTI exposure was associated with increased rates of congenital anomalies and use of INSTI during pregnancy was associated with preeclampsia. These findings underscore the need for continued monitoring of the safety of INSTI in pregnancy.